2019
DOI: 10.3847/1538-4357/ab2b46
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic Census of X-Ray Systems in the COSMOS Field

Abstract: We investigate spectroscopic properties of galaxy systems identified based on deep X-ray observations in the COSMOS field. The COSMOS X-ray system catalog we use (George et al. 2011) includes 180 X-ray systems to a limiting flux of 1.0 × 10 −15 erg cm −2 s −1 , an order of magnitude deeper than future e-ROSITA survey. We identify spectroscopic members of these X-ray systems based on the spectroscopic catalog constructed by compiling various spectroscopic surveys including 277 new measurements; 137 X-ray system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 105 publications
(194 reference statements)
1
10
0
Order By: Relevance
“…Based upon a cleaned sample of 74 groups, ref. [143] showed that the relation for individual groups appears to follow a shallower relation than clusters (consistent with that found by previous studies, e.g., [137]). However, they note that this trend may be affected by a small number of groups that appear to have anomalously low velocity dispersions (at σ v 125 km s −1 ) for their measured X-ray luminosity (discussed further in Section 3.4).…”
Section: The Luminosity-velocity Dispersion Relationsupporting
confidence: 91%
See 4 more Smart Citations
“…Based upon a cleaned sample of 74 groups, ref. [143] showed that the relation for individual groups appears to follow a shallower relation than clusters (consistent with that found by previous studies, e.g., [137]). However, they note that this trend may be affected by a small number of groups that appear to have anomalously low velocity dispersions (at σ v 125 km s −1 ) for their measured X-ray luminosity (discussed further in Section 3.4).…”
Section: The Luminosity-velocity Dispersion Relationsupporting
confidence: 91%
“…One observation made by various authors studying the L x -σ v relation, is the presence of low velocity dispersion groups (appearing at σ v 200 km s −1 ) that have a high X-ray luminosity in comparison to their σ v (conversely, it can be stated that these groups have a low σ v for their L x ). These low velocity outliers have been noted in various studies in the literature (e.g., [137,162]), attributed as the cause of the flattening of the L x -σ v relation at the group scale (e.g., Vajgel et al [149], Sohn et al [143]). Although it has been shown in Section 3.2 that the group scale relations may be consistent with self-similar predictions when accounting for the differing emissivity, the presence of these outliers are extreme cases.…”
Section: Low Velocity Dispersion Groupsmentioning
confidence: 77%
See 3 more Smart Citations